Protocol for a Pragmatic Trial of Pharmacotherapy Options Following Unsatisfactory Initial Treatment in OCD (PROCEED) - Wang, Pei; Gu, Wenjie; Gao, Jian; Wang, Changhong; Fang, Jianqun; Hu, Maorong; Xiang, Hui; Li, Bin; Liu, Na; Tang, Wenxin; Wang, Xijin; Jia, Yanbin; et al. (Frontiers in Psychiatry, 2022)
Background: Selective serotonin reuptake inhibitors (SSRIs) are the first-line pharmacotherapy for obsessive-compulsive disorder (OCD), but a large proportion of patients do not achieve remission after an adequate SSRI trial. To the best of our knowledge, there have been no well-powered randomized controlled trials (RCTs) of sequenced pharmacotherapy using pragmatic research designs. China provides a unique context for undertaking such a trial that will recruit the largest treatment-naïve participants and systematically compare the efficacy of different sequenced pharmacotherapy. Methods: A pragmatic research design will be adopted, with n=1600 treatment-naïve OCD patients initially treated for sertraline for 12 weeks, and with non-remitters then randomized to 5 different augmentation or switching pharmacotherapy options for another 12 weeks. The 5 arms will include: 1) treatment with higher than usual doses of sertraline, 2) switch to fluvoxamine, 3) switch to venlafaxine, 4) augmentation with memantine, and 5) augmentation with aripiprazole. Discussion: China is uniquely positioned to recruit sufficiently large sample sizes of treatment-naïve OCD patients to compare different pharmacotherapy options; data from the proposed trial promises to help inform current clinical practice guidelines by providing important information about optimal pharmacotherapy choice for those who demonstrate no response or response but no remission to first line pharmacotherapy. Trial Registration The trail was registered on 27 August 2020 in ClinicalTrials.gov (https://register.clinicaltrials.gov/) (NCT04539951). Keywords Obsessive-compulsive disorder, treatment-naïve, pharmacotherapy, alternatives, remission